LDB2 regulates the expression of DLL4 through the formation of oligomeric complexes in endothelial cells - Choi, Hyun-Jung; Rho, Seung-Sik; Choi, Dong-Hoon; Kwon, Young-Guen (BMB reports, 2018)
Delta-like ligand 4 (DLL4) expression in endothelial cells is intimately associated with angiogenic sprouting and vascular remodeling, but the precise mechanism of transcriptional regulation of DLL4 remains incompletely understood. Here, we showed that LIM-domain binding protein 2 (LDB2) plays an important role in regulating basal DLL4 and VEGF-induced DLL4 expression. Knockdown of LDB2 using siRNA enhanced endothelial sprouting and tubular network formation in vitro. Injection of ldb2-morpholino resulted in defective development of intersegmental vessels in zebrafish. Reduction or overexpression of LDB2 in endothelial cells decreased or increased DLL4 expression. LDB2 regulated DLL4 promoter activity by binding to its promoter region and the same promoter region was occupied and regulated by the LMO2/TAL1/GATA2 complex. Interestingly, LDB2 also mediated VEGF-induced DLL4 expression in endothelial cells. The regulation of DLL4 by the LDB2 complex provides a novel mechanism of DLL4 transcriptional control that may be exploited to develop therapeutics for aberrant vascular remodeling. [BMB Reports 2018; 51(1): 21-26].